The Hunger Games: A Systematic Review of Pediatric Bariatric Surgery - Arianne N. Theodorous; David M. Schwartzberg; Sathyaprasad C. Burjonrappa (Journal of Pharmacy and Nutrition Sciences, 2015)
Introduction: As childhood obesity in the US reaches alarming levels, bariatric surgery is becoming a more commonly implemented treatment option due to its high success rate compared with behavioral modification and medical therapy alone. The mechanisms by which it affects body weight and metabolic homeostasis are not well understood. The goal of the present study was to perform a systematic review of pediatric bariatric surgery to evaluate its effectiveness in the context of the physiologic changes that are produced. Materials and Methods: The PubMed database, MEDLINE, Springer Link, Cochrane, and article bibliographies were used to identify original English-language articles published between 2009 and 2014 evaluating pediatric patients. Included studies evaluated patients undergoing Roux en Y gastric bypass, laparoscopic sleeve gastrectomy or laparoscopic adjustable gastric banding and analyzed weight loss, BMI reduction, postoperative complications and co-morbidity resolution post-procedure; all articles had at least a one year follow up. Results: Five studies were included in our evaluation of the three most common bariatric procedures currently performed on the pediatric population for a total of 1,395 patients. The average patient age was 18.2 and 72% of patients were females. Most patients underwent roux en Y gastric bypass (RYGB) (n=659), followed by laparoscopic adjustable gastric banding (LAGB) (n=554) and finally laparoscopic sleeve gastrectomy (LSG) (n=149). The greatest decrease in BMI was seen in the RYGB group who lost an average BMI of 16.7kg/m2, followed by the LSG group with a loss of 14.0kg/m2. The LAGB patients lost 8.2kg/m2. Postoperative complications varied in severity, however the only death occurred in a patient following RYGB. Conclusion:Bariatric surgery has proven to reduce BMI and weight in the adolescent population resulting in an enhanced quality of life and resolution of significant co-morbidities. The mechanism of weight loss is different among the three most common procedures, as is their affect on gut hormone profiles. Ghrelin may have an effect on weight loss, however it is not solely responsible for the procedures’ weight loss effect as levels vary postoperatively. RYGB has been shown to produce the greatest weight loss but postoperative ghrelin levels are not consistently decreased compared to LSG, which demonstrates low ghrelin levels routinely. Additional studies are needed to measure weight loss as it relates to postoperative gut hormone levels, as determining the physiologic changes after these procedures will guide future therapies.